Women in God's Army : gender and equality in the early Salvation Army - Eason, Andrew Mark, 1966- (Etudes sur les femmes et la religion, 2003)
The early Salvation Army professed its commitment to sexual equality in ministry and leadership. In fact, its founding constitution proclaimed women had the right to preach and hold any office in the organization. But did they? Women in God's Army is the first study of its kind devoted to the critical analysis of this central claim. It traces the extent to which this egalitarian ideal was realized in the private and public lives of first- and second-generation female Salvationists in Britain and argues that the Salvation Army was found wanting in its overall commitment to w.